2019
DOI: 10.1111/ijd.14689
|View full text |Cite
|
Sign up to set email alerts
|

CD8+ cytotoxic mycosis fungoides: a retrospective analysis of clinical features and follow‐up results of 29 patients

Abstract: Background and objective Less than 5% of cases of mycosis fungoides (MF) present with a cytotoxic/suppressor CD8 + phenotype. This study aimed to evaluate the clinical characteristics, treatment modalities, and clinical course in CD8 + MF patients.Methods In a retrospective analysis of 353 MF patients in a referral center at Ankara University, Turkey, 29 patients that were diagnosed with CD8 + MF were included in the study.Results CD8 + MF cases constituted 8.2% of all MF patients. The age at the time of diagn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 33 publications
0
4
0
3
Order By: Relevance
“…It is essential to differentiate MF from other epidermotropic lymphomas, such as gamma–delta T-cell lymphoma and primary cutaneous CD8 + aggressive epidermotropic cytotoxic T-cell lymphoma. 36 These variants can be distinguished based on their unique immunoprofiles and clinicopathologic correlations. Other benign conditions that can mimic MF include actinic reticuloid and lichen planus-like keratosis.…”
Section: Discussionmentioning
confidence: 99%
“…It is essential to differentiate MF from other epidermotropic lymphomas, such as gamma–delta T-cell lymphoma and primary cutaneous CD8 + aggressive epidermotropic cytotoxic T-cell lymphoma. 36 These variants can be distinguished based on their unique immunoprofiles and clinicopathologic correlations. Other benign conditions that can mimic MF include actinic reticuloid and lichen planus-like keratosis.…”
Section: Discussionmentioning
confidence: 99%
“…Massone et al evaluated 73 specimens from 68 patients with early-stage disease at diagnosis (either stage Ia or Ib), and suggested that at early stages, CD8+ MF does not behave differently to CD4+ MF, and does not necessarily have a worse prognosis [ 24 ]. However, another study highlighted the fact that CD8+ MF is not a single entity, but rather a ‘mixed-bag’ of presentations, with some having more indolent courses similar to the typical CD4+ MF, such as those with hypopigmented patches often found in the younger population, and others demonstrating a more aggressive course [ 25 , 26 ]. Other studies comparing CD8+- and CD4+-predominant MF cohorts, suggest that CD8+ MF has a more indolent course, and suggest a treatment approach limited to skin-directed therapies and observation, for most patients [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…С и с т е м н а я т е р а п и я ГКС на очень ранних стадиях заболевания дают в среднем почти 50% общего ответа, возможно их сочетание с топическими ретиноидами [8 , 36,37]. Кроме того, при необходимости системного лечения агрессивных форм заболевания исполь зуют такие препараты, как липосомальный доксорубицин, брентуксимаб ведотин, ифосфамид, этопозид, гемцитабин.…”
Section: различные формы гм у детейunclassified